Enhancing Engagement through Gamification in Malaysian Blended Learning - Othman, Mohd Zailani; Daud, Shahreena; Taib, Norraeffa Md; Hasbullah, Nornajihah Nadia; Yazid, Zarinah Abu (International Review of Management and Marketing, 2025)
The transition to blended learning in Malaysia’s higher education system, particularly following the COVID-19 pandemic, has brought student engagement and participation to the forefront of educational challenges. This study investigates the potential of gamification as a tool to enhance student engagement, with a specific focus on perceived usefulness as a critical factor. Research design, data and methodology: Utilising the Gamification Acceptance Model (GAM), an extension of the Technology Acceptance Model (TAM), the research analyses survey data collected from 200 undergraduate students enrolled in the Strategic Management course at Universiti Teknologi MARA (UiTM) Kampus Bandaraya Melaka. Results: The findings indicate that perceived usefulness significantly enhances three dimensions of engagement: attitude, interactive engagement, and skill engagement. However, the mediating role of attitude in the relationship between perceived usefulness and engagement was not substantiated. These results underline the applicability of GAM in blended learning environments and emphasise the importance of perceived usefulness in directly fostering student engagement. Conclusions: The study provides useful advice to educators and higher education institutions, advocating for the integration of gamification into course designs to create more engaging and effective learning experiences.